Fatkhurrokhman - Muzakar Isa; Aflit Nuryulia Praswati; Nelly Purnama Sari; Eka Risky Widyawati (Prosiding University Research Colloquium, 2022)
Economic development through empowering SMEs needs to look at several important things, because basically SME actors still have some limitations so they need assistance and education to improve the quality of Human Resources so that the businesses they run can survive and continue to grow. The lack of ability to manage products, marketing and finance is the biggest obstacle faced by SMEs today, even though the ability of SMEs to manage their products and finances is the key to success for an entrepreneur. The problem faced in the financial sector is that if SMEs cannot manage their finances properly, it will cause various problems for business continuity. The problems faced besides finance are in terms of products and promotions. Often MSME actors do not pay attention to the packaging design of the product itself, even though the product packaging design affects the price of the product itself. The purpose of this service is to educate SMEs to carry out financial records and design packaging for SME products in Kahuman Village. The number of participants was 13 SMEs, all of which were classified as Small and Medium Industries.